Implementasi Algoritma Fisher-Yates Shuffle Pada Game Edukasi Aksara Jawa Menggunakan Godot Engine - Paulus Harsadi; Wawan Laksito Yuly Saptomo; Candra Yanu Wardhana (STMIK Sinar Nusantara, 2022)
Game is one of the implementations of the computer science field which has developed very rapidly. Game is also a form of educational application, meaning that it can be used as a learning media where the process can be carried out with the 'learning while playing' concept for children.The utilization and use of 'Aksara Jawa' educational game can support the learning process of the children when they want to learn while playing to recognize 'Aksara Jawa'. This 'Aksara Jawa' educational game is a game that is designed to improve children's ability to memorize and understand 'Aksara Jawa'. This game contain questions that need to be answered by players by arranging the scrambled 'Aksara Jawa' to form the correct words or sentences. The used algorithm is Shuffle Random which players can't memorize the position of 'Aksara Jawa' and make the game not boring, and also able to apply 'learning and playing' system and become a good learning method among the children. In this study, Shuffle Random Algorithm was used to randomize the 'Aksara Jawa' contained in every questions which were packaged in the form of a game. The making of this 'Aksara Jawa' educational game was using Godot engine software and GDscript programming language. The final result of this research is that this game can help to learn to memorize, so that it can train reasoning and memory power, and also can be used as a means of entertainment.